Studi Awal Sonifikasi Pada Data Gerak Parabola Berbantuan Arduino Uno R3 Atmega328 - Yudhiakto Pramudya; Riza Hayyuningtias (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2022)
Parabolic motion is the typical phenomenon in classical mechanics. The students are able to understand the concept by reading the data in the parabolic function. However, there is limited material for visual impaired students to study the parabolic motion data. One of the solutions to overcome this problem is the parabolic motion experiment development using sonification method. Research has been carried out to analyze the accuracy of the frequency produced by the speakers in data conversion assisted by Arduino Uno. The research also analyzes the effect of elevation angle variations on the resulting frequency changes. The data collection process is carried out by analyzing the percentage of accuracy using the average technique of the data recorded by the Phyphox application. The data analysis of the Phyphox application is compared with the data obtained from the Tracker application. From the results of data analysis obtained the percentage value of the velocity for the angle 30o, 45o, and 70o were 99.92%, 99.67%, and 98.42%, respectively. Therefore, it can be said that the preliminary sonification study is feasible to be used in physics experiments on parabolic motion learning, especially for visual impaired students. The final plotting result of this research shows that the frequency versus time at each angle produces a graph in the parabolic form. While the effect of angle variations on frequency changes is that the larger the angle, the slower it will reach the peak frequency.